Strategy for Improving the Economy of MSMEs in Ngagel Village Through the "Local Biz Day" Program - Diyah Ayu Putri Aprilia; Fernanda Aurellia Putri Mukhlasin; Najwa Tsaniya Anjainah; Dita Atasa; Zainal Abidin Achmad (Unram Journal of Community Service, 2025)
The Local Biz Day program is a community service initiative aimed at empowering Micro, Small, and Medium Enterprises (MSMEs) in Ngagel Village, Surabaya. This activity includes product innovation training, digital marketing strategies, and an MSME stand design exhibition as a form of capacity building for local businesses. This study uses a descriptive qualitative approach with SWOT, IFAS, and EFAS analysis methods to evaluate the program's effectiveness. The analysis results indicate that the program is pursuing a growth-oriented strategy, with strengths and opportunities more dominant than weaknesses and threats. In addition to increasing MSME competitiveness, this program also supports the achievement of SDGs points 4, 8, 9, and 11 through an educational, innovative, and participatory approach.